2018
DOI: 10.1183/13993003.01355-2016
|View full text |Cite
|
Sign up to set email alerts
|

How to build a lung: latest advances and emerging themes in lung bioengineering

Abstract: Chronic respiratory diseases remain a major cause of morbidity and mortality worldwide. The only option at end-stage disease is lung transplantation, but there are not enough donor lungs to meet clinical demand. Alternative options to increase tissue availability for lung transplantation are urgently required to close the gap on this unmet clinical need. A growing number of tissue engineering approaches are exploring the potential to generate lung tissue for transplantation. Both biologically derived and manuf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 169 publications
(232 reference statements)
0
41
0
Order By: Relevance
“…Furthermore, it has been shown that decellularized extracellular matrix (dECM) containing essential proteins for cell attachment and proliferation, could be a good candidate to improve the biocompatibility of copolymers . In a recent study, hybrid electrospun scaffold of poly‐L‐lactic acid and dECM (derived from pig lung) for in vitro ASM model showed that dECM improved physical characteristics (e.g., wettability) …”
Section: Alveolar‐capillary Basement Membrane For Ali Cell Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been shown that decellularized extracellular matrix (dECM) containing essential proteins for cell attachment and proliferation, could be a good candidate to improve the biocompatibility of copolymers . In a recent study, hybrid electrospun scaffold of poly‐L‐lactic acid and dECM (derived from pig lung) for in vitro ASM model showed that dECM improved physical characteristics (e.g., wettability) …”
Section: Alveolar‐capillary Basement Membrane For Ali Cell Culturesmentioning
confidence: 99%
“…The hydrophilicity, biocompatibility, and mechanical properties (Young's modulus: 1.77 ± 0.09 MPa) of these hybrid materials make them promising membrane materials for lung models, although they have not been widely applied in lung research, yet. dECM‐derived native lung tissue, a biomimetic mixture of natural ECM proteins, is another promising natural material because of its excellent biocompatibility features, although it does not have sufficiently biomimetic mechanical properties . As this deficiency can be compensated by hybridization with a synthetic polymer, several synthetic/dECM copolymers have been recently manufactured for tissue engineering application …”
Section: Future Directions: Biomimetic Models Of the Lungmentioning
confidence: 99%
“…The ECM is one of the major constituents in whole-organ decellularized scaffolds that are being explored for ex vivo engineering of lung tissue. Although a number of key hurdles have been overcome (e.g., protocols to decellularize human and large animal scaffolds, expansion of cells for re-endothelialization and re-epithelialization of whole human and large animal constructs) ( 29 ), a number of challenges remain. Recent work by Dr. Harald Ott’s group in a short-term porcine model of transplantation has identified a number of key hurdles, including achievement of higher-level cellular function such as surfactant expression.…”
Section: Methodsmentioning
confidence: 99%
“…A promising area of research is the (re)generation of pulmonary tissue using ex vivo bioengineering methods. In these approaches, cells are combined with a scaffold outside of the body, with the goal of forming new tissue for transplantation [106]. Scaffolds can be derived from either biological or artificial materials (or a combination thereof in hybrid approaches) and could be seeded with an appropriate cell source to regenerate functional lung tissue for subsequent transplantation.…”
Section: Exogenous Regenerationmentioning
confidence: 99%